Aesthetics of the margins - the margins of aesthetics wild art explained - Carrier, David 1944-; Pissarro, Joachim 1959- (The Pennsylvania State University Press, 2018)
"Examines art that stands outside the margins of the art world, the critical and cultural conditions that made this exclusion possible, and how its recognition radically transforms our understanding of contemporary art" ... Provided by publisher
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Aesthetics, Modern; Art, Modern; Kunst; Ästhetik